Pengambilan Keputusan dalam Pemilihan Sayuran Untuk Memenuhi Kebutuhan Konsumsi Rumah Tangga - Puspitasari, Anisa; Kurniawati, Tiktiek (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
A yard is a plot of land around the house that is easy to cultivate with the aim of increasing the fulfillment of micronutrients through improving the family menu. Efforts to improve family food security and community nutrition must begin with the utilization of resources that are available and that can be provided in the environment. The responses obtained in this study were 185 households. The aim of this research is to find out how much understanding there is about the use of yard land. And to find out decision making in selecting vegetables. The sampling technique used was simple random sampling. The analytical method used consists of qualitative descriptive analysis to determine knowledge of yard land use, and descriptive statistics to determine decision making in selecting vegetables. The results of the research show that 67.76% have consumed vegetables from the produce of the yard, but 84.43% still buy vegetables outside for consumption, this is because growing vegetables in the yard is still not diverse enough to meet other types of vegetable food, so it is necessary to buy vegetables others to create a diversity of types of vegetables consumed. The decision to consume vegetables is influenced by housewives. The research results show the importance of consuming vegetables because of the benefits and taste of vegetables for 95.65% of respondents. Most respondents are not fixated on one type of vegetable, the most influential satisfaction factor is vegetables because of the ease of obtaining vegetables with a percentage of 42.31 and the price is quite affordable with a percentage of 38.96%. The results of the study showed that respondents did not know enough about the importance of the nutrients contained in vegetables, 30.54 respondents consumed vegetables less than 250 grams/day, this is not in accordance with WHO recommendations, because consuming vegetables can contribute to fulfilling nutrients that are important for the body because Vegetables contain vitamins, mineral and fiber that the body needs.